Variability of Some Meteorological Elements During the Southwest Monsoon Season in Bangladesh (Journal of Bangladesh Academy of Sciences, 2016)
Statistical computation and analysis of the co-efficient of variation of different meteorological parameter such as mean sea level pressure, rainfall, dew-point depression, minimum temperature and maximum temperature over Bangladesh during the onset, on-going and withdrawal phases of southwest monsoon, season of 1981- 2010 was dealt with. The study reveals that the coefficient of variation of the mean sea level (msl) pressure is practically small over Bangladesh during the onset and ongoing phases of southwest monsoon. During the onset phase, the CV of msl pressure is relatively higher and decreases during the on-going phase. The variation of msl pressure increases slightly in the withdrawal phase of monsoon. The ranges of CV of msl pressure are 0.064 - 0.197%, 0.079 - 0.809%, 0.091 - 0.793%, 0.069 - 0.272%, 0.0695 - 0.229% and 0.127 - 0.32% in May, June, July, August, September and October, respectively. The variation of dew-point depression decreases in the eastern part during the onset phase of southwest monsoon and becomes lower all over Bangladesh during the on-going phase of monsoon. It again increases during the withdrawal phase. The maximum co-efficient of variation of rainfall exists over the southeastern part of Bangladesh during the on-going phase of southwest monsoon and decreases in June and July over Bangladesh i.e. during the early on-going phase of monsoon. The co-efficient of variation of minimum and maximum temperatures is found to decrease during the onset and on-going phases of southwest monsoon and increases during the withdrawal of monsoon from Bangladesh.Journal of Bangladesh Academy of Sciences, Vol. 40, No. 2, 155-167, 2016